Essential problems of control in physical education of students in high education established - Dukh T.I; Bodnar I.R (Kharkov National Pedagogical University, 2012)
It is analysed rating of the most essential and more often applied types of control in physical education of higher educational establishments of Ukraine. A questionnaire was conducted 156 teachers of departments of physical education of higher institutions of Ukraine and expert estimation was done. It is set that to self-control and two-way control of students on employments on physical education of higher educational establishments spared unjustified small time. It is found out that the level of readiness of teachers to realization of different types of control in physical education is estimated as below with.